The Muslim, state and mind : psychology in times of Islamophobia - Younis, Tarek (London : SAGE Publications Ltd, 2024)
Mental health is positioned as the cure-all for society's discontents, from pandemics to terrorism. But psychology and psychiatry are not apolitical, and neither are Muslims. This book unpacks where the politics of the psy-disciplines and the politics of Muslims overlaps, demonstrating how psychological theories and practices serve State interests and perpetuate inequality-especially racism and Islamophobia. Viewing the psy-disciplines from the margins, this book illustrates how these necessarily serve the State in the production of loyal, low-risk and productive citizens, offering a modern discussion of three paradigms underlying the psy-disciplines: neoliberalism, security and the politics of mental health. Tarek Younis is Senior Lecturer in Psychology at Middlesex University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Muslims -- Mental health; Muslims -- Persecutions; Muslims -- Political aspects; Religion and politics; Psychology and religion